Teacher's Understanding of the Scientific Approach in the 2013 Curriculum for Early Childhood Education - Rohita Rohita; Nila Fitria; Radhiya Bustan; Dody Haryadi (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2018)
The purpose of this study was to determine the teacher's understanding of the scientific approach in the 2013 PAUD curriculum. The method used is a survey with data collection techniques using a questionnaire. Respondents were 100 teachers from 100 TK in 5 DKI Jakarta regions. The conclusion of this study is that the understanding of the kindergarten teacher about the 2013 curriculum of PAUD is in the category of meaningful interpreting not only the transfer of meaning from one language into another language but also from an abstract conception to become a model, namely a symbolic model to make it easier for people to learn, in terms it is easy to learn concept of the scientific approach which includes 5 scientific steps, namely observing, asking, gsthering information, reasoning, and communocating, so that it will be easy to learn and apply in the learning process which is characterized by 61% of respondents able to explain the scientific approach, and 7.14% of respondents able describe the scientific approach to RPPH correctly